Strategi Kua Kecamatan Sungai Menang Dalam Menangani Dampak Pernikahan Dini Melalui Pendekatan Proaktif (Studi Kasus Pada Masyarakat Kecamatan Sungai Menang Kabupaten Oki) - Warida Muslika Wahid Suwoto; Candra Darmawan (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "This thesis is entitled "The Strategy of the KUA of Sungai Menang District in Handling the Impact of Early Marriage through a Proactive approach (In a Case Study of the Community of Sungai Menang District, OKI Regency)". This research is motivated by the large number of early marriages and the lack of public awareness about the negative impact of early marriage in Sungai Menang District. The purpose of this research is to find out what strategies are carried out by KUA employees and counselors in Sungai Menang Sub-district in dealing with the impact of early marriage and to find out what factors can influence public awareness of the impact of early marriage through a proactive approach. This type of research uses a qualitative approach with a descriptive approach. The data collection techniques include observation, interviews, documentation using primary and secondary data. While in the data analysis technique used interactive analysis, namely data reduction, data presentation and conclusion drawing. This research data uses the Impact of Early Marriage Theory popularized by Ngiyatul Khasanah and the KUA Strategy Theory popularized by Ayu Rahadianti and Azis Muslim. Based on the results of this study, there are still many people who enter into early marriage with various factors that occur, lack of public awareness of the impact of early marriage, and people who ignore the advice given by the extension workers, However, there are also people who understand and understand the impact of early marriage so that they do not enter into early marriage and the strategies carried out by the KUA have an impact on prospective brides who will register for marriage. Thus, the KUA strategy and extension activities carried out by the extension workers can be carried out well and smoothly, then people should realize and understand what the impact will be if they enter into early marriage.